Novel idiotypic and antigen-binding characteristics in two anti- dinitrophenyl monoclonal antibodies (The Rockefeller University Press, 1977)
Monoclonal anti-dinitrophenyl antibodies generated in the splenic focus system from B cells of adult BALB/c mice were studied for the presence or absence of murine anti-T15 (M anti-T15) reactivity and for their ability to bind phosphorylcholine (PC). Two foci of the 680 clones analyzed bound PC, and one of these antibodies reacted with M anti-T15 and anti-Fab on a 1:1 weight basis. The discovery of a clonotype reactive with M anti-15 but not with rabbit anti-T15 (R anti-T15) serum, the converse of the R anti-T15+, M anti-T15- clonotype identified in the PC-specific repertoire, points to the novel idiotypic relationships which may be found among homogeneous antibodies binding diverse antigens. The R anti-T15-, M anti-T15+ clonotype may represent a distinct set of hypervariable region sequences inserted into the T15 framework or may be a somatic variant of the T15 germ-line sequence. In addition, the maximum frequency with which this clonotype occurs within the B-cell pool is estimated.